Project SUMS (scaling up of mental health in schools): design and methods for a pragmatic, cluster randomised waitlist-controlled trial on integrated school mental health intervention for adolescents - Senthil Amudhan; Kavita Jangam; Kalaivani Mani; Nithya Poornima Murugappan; Eesha Sharma; Payel Mahapatra; Ajit Deo Burma; Hemant Kumar Tiwari; Ashi Ashok; Sangappa Vaggar; Girish Nagaraja Rao (BMC, 2021)
Abstract Background There is an increasing need for Mental Health Promotion (MHP) among adolescents, especially in developing countries with limited resources and rapid socio-demographic transition. With the growing burden of mental health problems among adolescents (suicide, depression) and their preferences to seek help from their peers, improving Mental Health Literacy (MHL) and behaviours for First Aid in Mental Health (MH-FA) becomes crucial to promote their mental health. Methods Schools are ideal settings for reaching the vulnerable adolescents. The proposed study evaluates the effectiveness of a classroom-based teacher-led integrated school mental health intervention called SUMS (MHP + MHL + MH-FA). The study will involve a pragmatic, cluster-randomised waitlist-controlled design to evaluate the effectiveness of SUMS intervention using schools as unit-of-randomisation. The study will be conducted in Srinivaspura taluka (Sub-district) of Kolar district (administrative unit of health) of Karnataka in collaboration with a multi-disciplinary expert team from NIMHANS (National Institute of Mental Health And Neuro Sciences), Bangalore-India and Department of Education, Government of Karnataka, India. A total of 8 schools (400 students studying in 6-8 grade) from Srinivaspura taluka will be randomised into intervention and waitlist control group. The intervention group will receive SUMS intervention through 10-15 h of classroom sessions. The primary outcome is the improvement in positive mental health literacy, as measured by the Mental Health-Promoting Knowledge (MHPK-10) scale. Changes in MH-FA knowledge and intentions, Mental health stigma, help-seeking and resilience are assessed as secondary outcomes. Data will be collected at baseline, 6-weeks, 6-months and 12-months post-intervention. The waitlist-control schools will receive the interventions at the end of the 12-month follow-up assessment in intervention-schools. Discussion This is the first study to integrate Mental Health Literacy with Mental Health Promotion and behaviours for First Aid in Mental Health to promote mental health well-being among adolescent school children in India. With a need to build a more substantial evidence base on School Mental Health Promotion approaches in developing countries, the study findings will have implications for implementing and operationalising Health and Wellness Ambassador initiative in India. Trial registration Clinical Trials Registry - India, CTRI/2019/07/020394. Registered prospectively on 29 July 2019. ( ctri.nic.in/Clinicaltrials/pmaindet2.php?trialid=35724&EncHid=&userName=sums ).